Sliding-mode disturbance observers for an artificial pancreas without meal announcement. (June 2019) - Sala-Mira, Iván; Díez, José-Luis; Ricarte, Beatriz; Bondia, Jorge
Highlights: The proposed observer enhances linear methods in estimating glucose appearance rate. Best tradeoff between sensitivity and early meal detection: 92.4%, 28.5 min. Non-significant mean glucose is found regarding hybrid system with carbs miscounting. Abstract: Carbohydrate counting is not only a burden for patients with type 1 diabetes, but estimation errors in meal announcement could also degrade the outcomes of the current hybrid closed-loop systems. Therefore, removing meal announcement is desirable. A novel control system is addressed here to face postprandial control without meal announcement. The proposed system grounds on two applications of the sliding mode observers in dealing with disturbances: first, the equivalent output technique is used to reconstruct the meal rate of glucose appearance via a first order sliding mode observer; second, a super-twisting-based residual generator is used to detect the meals. Subsequently, a bolusing algorithm uses the information of the two observers to trigger a series of boluses based on a proportional-derivative-like strategy. An in silico validation with 30 patients in a 30-day scenario reveals that the meal detector algorithm achieves a low rate of false positives per day (0.1 (0.1), mean (SD)) and a detection time of 28.5(6.2) min. Additionally, the bolusing algorithm fulfills a non-statistically different mean glucose than the hybrid counterpart with bolus misestimation (146.69 (12.20) mg/dL vs. 144.28 (11.01) mg/dL, p >0.05), without increasing hypoglycemia (0.029 (0.077) vs. 0.004 (0.014)%, p > 0, 05), although at the expense of a slightly higher time in hyperglycemia (22.51(8.72) % vs. 18.65 (7.89)%, p < 0.05 ) due to the conservative tuning of the bolusing algorithm for the sake of safety.